Problems in Diagnosis Approach for Carcinoma of Pancreatic Head - Ratu Ratih Kusumayanti; Marcellus Simadibrata; Murdani Abdullah; Rino Alvani Gani; Lies Luthariana (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2008)
Incidences of pancreatic cancer worldwide have been known to be increased. It is the fifth leading cause of death in United State of America. Seventy percent occurs in the head of the pancreas. Major risk factors are related to age, black race, smokers, high-fat diet, chronic pancreatitis, diabetes mellitus and alcohol consumption. Some clinical symptoms such as jaundice, abdominal pain, unexplained weight loss or ascites can occur early or even late in the course of disease. Diagnosing pancreatic cancer sometimes can be difficult, regarding to discrepancy between clinical symptoms and radiological findings. It is important to take good history of the patient, thorough examination, and combine several modalities in diagnosing tumor of pancreatic head. In this case report, a 54 year-old female, came to the hospital with abdominal swelling and jaundice. Physical examination revealed liver and spleen enlargement and edema on both lower extremities. The laboratory result showed increment in Carcinoembryonic Antigen (CEA) and carbohydrate antigen 19-9 (CA19–9) level, without marked increase in bilirubin level. Dilatation of the pancreatic duct was found in this patient, without any sign of bile stone. Endoscopic Retrograde Cholangiopancreatography (ERCP) in this patient was failed to have significant result. Keywords: carcinoma of pancreatic head, papilla vater carcinoma, diagnosis, ERCP, jaundiceHF